The pagdadala model in counseling and therapy - Decenteceo, Edwin T. (1999)
Burden bearing (pagdadala), because it is an experience of the common Filipino, is used as a model (Pagdadala) for viewing the life experiences of the Filipino and used, as well, as a way to help the Filipino in difficult times. The Filipino is then revealed as committed to his or her tasks, responsibilities and relationships, taking these to their destinations, crawling on hands and knees if needed. The Filipino is seen to gain meaning not only from fulfilling accountabilities but also from a sense of belonging to a community of co-burden bearers that in return gives meaning to acts of burden bearing.. The model also reveals ways of helping a burden bearer in difficulty which allow a helper to move sensitively with the burden bearer. Some issues are clarified; issues of self, of being with the other, of bearing up, of letting out breath when tires, and of seeing things in different ways. Finally, the counselor is then seen as someone who has taken up the burden of helping co-burden bearers.
Includes bibliographical references (page 104).